Agriculture Portal for Decsion making, Plantation and Marketing of Crops - RS, Gayathri; CN, Mangala (International Journal of Computer Sciences and Engineering, 2025)
India is said to be a land of agriculture. Engineering techniques in agriculture brings a lot of advantages to the farmer. The proposed system aims to provide support to farmers during all three stages of farming preprocessing, plantation and post production. Preproduction support includes providing the various crop demand information to farmers through android application. The plantation support includes the automation in monitoring of crops and post production support includes providing the information regarding the market rates for every crop. Preproduction support has an algorithm that calculates the crop demand in real time considering the crop demand input from the surveys and the crops grown by various farmers. This information will be made available to farmers to help them choose the crop that is in demand and hence get a good profit at the end. The plantation support includes automatic irrigation based on dryness of land. The other plantation support includes the intruder detection, providing temperature sensing, humidity sensing and intruder detection. The post production support includes providing information regarding the market rate for various crops on their android phones